2018
DOI: 10.4103/ijn.ijn_158_17
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of kidney biopsy in Indian patients older than 60 years: A tertiary care experience

Abstract: The adult population above the age of 60 years has significantly increased in India, with a life expectancy of 68.4 years in 2016. Data regarding the renal histopathology in these patients are scarce though the number of native kidney biopsies done in this subset of population is increasing. The present study is a retrospective analysis of 231 biopsies from a total of 700 biopsies, from patients above 60 years of age (M = 65.8%; F = 34.2%) with a mean age of 64 ± 6.03 years. The indications for kidney biopsy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
3
4
1
Order By: Relevance
“…Males dominated our biopsy cohort making up to 70%, a finding noted by other Indian studies as well. [ 15 16 17 ] Nephrotic syndrome was the most common indication for elderly patients to undergo renal biopsy, a finding consistent with other Indian [ Table 2 ] and western studies. [ 18 20 ] MGN was the commonest cause of nephrotic syndrome followed by amyloidosis.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Males dominated our biopsy cohort making up to 70%, a finding noted by other Indian studies as well. [ 15 16 17 ] Nephrotic syndrome was the most common indication for elderly patients to undergo renal biopsy, a finding consistent with other Indian [ Table 2 ] and western studies. [ 18 20 ] MGN was the commonest cause of nephrotic syndrome followed by amyloidosis.…”
Section: Discussionsupporting
confidence: 86%
“…Almost 14% of the patients undergoing renal biopsy at our center were elderly. This is lower than the study from south India, which reported 30% elderly in their biopsy cohort[ 15 ] but is higher than that reported from north India[ 16 17 ] [ Table 2 ]. This proportion of the elderly population is lower than those of developed countries like Europe and the USA, where it contributes to about 23% and 25% of kidney biopsies, respectively.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In this review, we will focus on the clinicopathological characteristics of certain recurrent glomerular diseases: immunoglobulin A (IgA) nephropathy,[ 4 5 ] membranous nephropathy (MN),[ 5 6 ] focal segmental glomerulosclerosis (FSGS),[ 5 ] lupus nephritis, complement-mediated glomerulonephritis,[ 5 ] and some monoclonal gammopathy-related renal diseases.…”
Section: Introductionmentioning
confidence: 99%